2008
DOI: 10.1017/s0144686x08007083
|View full text |Cite
|
Sign up to set email alerts
|

Individual pension-related risk propensities: the effects of socio-demographic characteristics and a spousal pension entitlement on risk attitudes

Abstract: The transition from defined-benefit to defined-contribution occupational-pension plans has placed a premium on the participants' or contributors' decision-making competence. Their attitudes to risk and their responses to available investment options can have far-reaching implications for their retirement income. Behavioural research on risk and uncertainty has raised understanding of the limits of individual decision-making, but the social status and demographic characteristics of plan participants may also af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
86
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 53 publications
11
86
0
1
Order By: Relevance
“…The current complexity of the UK pension system (Clark and Strauss, 2008), combined with the length of time to retirement, can lead to difficulty identifying whether 'it pays to save' and whether that saving should be in the form of a pension (Berry, 2011). The benefits of saving for retirement are not always immediately obvious, especially when future needs are difficult to predict.…”
Section: Liam Fostermentioning
confidence: 99%
“…The current complexity of the UK pension system (Clark and Strauss, 2008), combined with the length of time to retirement, can lead to difficulty identifying whether 'it pays to save' and whether that saving should be in the form of a pension (Berry, 2011). The benefits of saving for retirement are not always immediately obvious, especially when future needs are difficult to predict.…”
Section: Liam Fostermentioning
confidence: 99%
“…In their research, they point out that perceived financial knowledge is essential for best practices and positive financial behaviours such as paying off credit card balances, having an emergency fund, and saving for retirement. According to Clark & Strauss (2008) and van Rooij et al (2007van Rooij et al ( , 2011, individuals' attitudes and perception of financial risks are determinants of a variety of financial decisions. Benjamin et al (2013) and Dohmen et al(2010) also proved that knowledge and cognitive ability affect preferences such as risk aversion, an impact on financial decisions.…”
Section: Actual and Perceived Financial Literacy And Financial Behaviourmentioning
confidence: 99%
“…The independent variables which are coded to represent actual financial knowledge are constructed based on the study conducted by van Rooij et al (2011) and Bateman et al (2012), a self-reported perception financial knowledge is constructed based on the study conducted by Australia & Financial Literacy Foundation, (2007), Financial risk tolerance measured in section three is based on questions devised by van Rooij et al (2007) and Clark & Strauss (2008), and demographic characteristics. The actual financial knowledge variable is each coded as a binary variable (1 = Correct, 0 = Incorrect).…”
Section: Measure the Variablesmentioning
confidence: 99%
“…Browning and Lusardi, 1996;Browning and Crossley, 2001) suggest that a deterioration of health status, a decrease of family size or increased mortality risk could reduce the marginal utility of consumption. Allowing for uncertainty, Banks, Blundell and Tanner (1998) argued that unanticipated shocks occurring around the date of retirement could explain the fall in spending within the context of the life-cycle model, while Bernheim, Skinner and Weinberg (2001) argued that workers do not adequately foresee the decline in income associated with the retirement or the risks associated with different retirement saving and pension schemes (Clark and Strauss, 2008). Hurst (2005, 2009) argued that when non-durable expenditures are disaggregated into detailed consumption categories, work-related expenditures account for most of the decrease in consumption.…”
Section: Introductionmentioning
confidence: 99%